2007
DOI: 10.1243/09544089jpme125
|View full text |Cite
|
Sign up to set email alerts
|

A simplified method for calculating the stress of a large storage tank wall

Abstract: With consideration of the influences from the constraint reaction of tank bottom plate to each shell course, a simplified long-short shell method was proposed to calculate the stress of a large storage tank wall. The first shell course was regarded as a short cylindrical shell while all the others as long cylindrical shells, and the analytic solution equations of shell stress were achieved by theory of plates and shells. With resistance stress-strain method, a field stress test was done on a 15×10 4 m 3 floati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Analysed on the new 15 × 10 4 m 3 oil tank with external-floating roof mentioned above, the stresses of tank shell and bottom plate are measured in accordance with reference [5]. Table 3 shows the measured values of radial stress on the upper surface of bottom plate when fully filled.…”
Section: Measured Stress On the Bottom Platementioning
confidence: 99%
“…Analysed on the new 15 × 10 4 m 3 oil tank with external-floating roof mentioned above, the stresses of tank shell and bottom plate are measured in accordance with reference [5]. Table 3 shows the measured values of radial stress on the upper surface of bottom plate when fully filled.…”
Section: Measured Stress On the Bottom Platementioning
confidence: 99%
“…22 Therefore, Wu 23 and Chen et al. 24 suggest simpler methods of analysis for calculating the bottom or shell of the tank. As a different approach, Zick and McGrath 25 have done detailed theoretical research to understand the stresses in the wall of cylindrical tanks and suggested a variable shell calculation adopted by the API.…”
Section: Introductionmentioning
confidence: 99%
“…The second method is much easier to use, with a large number of simplifications, which significantly affects its precision, especially for large diameter tanks. 22 Therefore, Wu 23 and Chen et al 24 suggest simpler methods of analysis for calculating the bottom or shell of the tank. As a different approach, Zick and McGrath 25 have done detailed theoretical research to understand the stresses in the wall of cylindrical tanks and suggested a variable shell calculation adopted by the API.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers worked on dynamic effects related to earthquakes [9][10][11]. Chen et al worked on developing a simple method to calculate shell stress [12].…”
Section: Introductionmentioning
confidence: 99%